2010
DOI: 10.1186/1471-2180-10-271
|View full text |Cite
|
Sign up to set email alerts
|

A bacteria-specific 2[4Fe-4S] ferredoxin is essential in Pseudomonas aeruginosa

Abstract: BackgroundFerredoxins are small iron-sulfur proteins belonging to all domains of life. A sub-group binds two [4Fe-4S] clusters with unequal and extremely low values of the reduction potentials. These unusual properties are associated with two specific fragments of sequence. The functional importance of the very low potential ferredoxins is unknown.ResultsA bioinformatic screening of the sequence features defining very low potential 2[4Fe-4S] ferredoxins has revealed the almost exclusive presence of the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…aeruginosa . Fdx1 has been shown to be essential for the viability of PAO1 [ 40 ]. The physiological role of Fdx1 in P .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aeruginosa . Fdx1 has been shown to be essential for the viability of PAO1 [ 40 ]. The physiological role of Fdx1 in P .…”
Section: Resultsmentioning
confidence: 99%
“…aeruginosa . An fdx1 encoding putative reaction partner of FprA is also an essential gene in PAO1 [ 40 ]. Thus, the link between FprA and Fdx1 is important to PAO1 physiology.…”
Section: Resultsmentioning
confidence: 99%
“…These novel proteins contain two [4Fe-4S] clusters of widely differing and very low redox potential (E 0 1 ϳ Ϫ650 mV; E 0 2 ϳ Ϫ450 mV) due to unique structural motifs (36). Elsen et al found evidence that the essential Alvin ferredoxin in Pseudomonas aeruginosa was likely not involved in the catabolism of aromatic compounds but instead that its gene had the constitutive expression characteristics of a housekeeping gene (37). It's essentiality in that organism showed that other redox paralogs could not substitute for its essential function.…”
Section: Discussionmentioning
confidence: 99%
“…Cells with higher levels of IscA protein might be more efficient in repairing and assembling damaged Fe-S proteins. Ferredoxins play an important role in a metabolism and are involved in electron transfer processes [5]. Oxidative stress down-regulates ferredoxin, and its overexpression can counteract this effect [8].…”
mentioning
confidence: 99%